Resilience and Growth Through Sustained Adjustment : The Moroccan Experience - Eken, Sena (Occasional Papers; Occasional Paper ;, 1995)
This paper reviews and analyzes how Morocco overcame the economic and financial crisis it confronted at the beginning of the 1980s. It highlights the challenges that still confront the Moroccan economy and the lessons that can be drawn from Morocco's adjustment experience.